Analysis of the Level of Satisfaction with the Use of Computer Assisted Test at SMAN 1 Parang Magetan - Aliyadi; Karaman, Jamilah (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The use of technology in education sector provides many conveniences in carrying out learning activities. One use of technology in the education sector can be used by teaching staff to carry out evaluations after carrying out a series of learning activities. The technology that can be used can be in any form, one of which is a system that is built to facilitate the learning process from start to finish. One system that can be used is the systemComputer Assisted Test (CAT). CAT is a system that uses computers as the main medium. In the CAT system, practice questions can be input which will be filled in by students later. This CAT system is used by students to work on practice questions. The system that has been used needs to be evaluated to determine its advantages and disadvantages. One method that can be used to analyze a system is the usability approach User Satisfaction Quesionnaire (UEQ). This approach uses user experience as the main aspect in system assessment and there are 6 variables assessed, namely Attractiveness (Daya Tarik), Efficiency (Efisiensi), Clarity (Tingkat Kejelasan), Dependability (Ketepatan), Stimulation (Stimulasi), and Novelty (Kebaruan). This research uses a UEQ questionnaire which will be filled in by 88 students and 12 teachers who act as research samples after working on practice questions through the CAT system. The completed questionnaire was then analyzed and it was discovered that for the Attractiveness, Efficiency, Clarity and Stimulation variables received the "Very Good" criteria, the Novelty variable "Good", and  the Dependability variable "Below Average".